Technological methods of herbs Salsola collina Pall. efficient processing - A. N. Melentiyeva; V. S. Chuchalin; V. N. Burkova (Бюллетень сибирской медицины)
Research is devoted to the problem of efficient use of the herbs of Salsola collina Pall. Studied and analyzed the known technological methods of processing and to obtain standardized extractive complexes. Had developed an effective method of obtaining the liquid extract. The parameters of the extraction process and the proposed complex extractant, allowing a high degree of depletion of plant material for the various groups of biologically active substances, and get the finished product with desired properties.